An Unsynchronized Measurements Correction Method for Two-Terminal Fault-Location Problems - Yu, Chi-Shan (IEEE transactions on power delivery, 2010)
This paper presents a method to correct the unsynchronized measurements for two-terminal fault-location problems. First, a synchronization index is defined to check whether the measurements are synchronized. A modified secant method-based algorithm is then developed to obtain a synchronization angle and correct the unsynchronized measurements. When the unsynchronized measurements are corrected, the fault location can be simultaneously obtained from the intermediate result of the proposed computation. Thus, although the proposed method is developed to correct the unsynchronized measurements, the fault-location problem can also be solved. Compared with the previous works, the proposed iteration equation is simpler. The MATLAB/SIMULINK simulator is used to evaluate the effectiveness of the proposed method.